Philosophical Review of Artificial Intelligence for Society 5.0 - Ggaliwango, Marvin; Tamale, Micheal; Kanagwa, Benjamin; Jjingo, Daudi (Springer Nature Singapore Pte Ltd., 2024)
Artificial intelligence has come a long way since its inception 60 years ago, and it continues to evolve and change the world in ways we couldn’t have imagined. Today, AI has reached new heights and has a wide range of applications, from playing complex games to language processing, speech recognition, and facial recog nition [1–3]. With its exponential growth and its increasing presence in an ever growing number of sectors, AI is well on its way to becoming a source of significant economic prosperity. But as AI continues to evolve, it poses major policy questions for policymakers, investors, technologists, scholars, and students. AI ethics are crit ical to its development, and it is essential that ethical standards be established to ensure that AI meets a certain standard of public justification and supports citizens’ rights, promoting substantively fair outcomes when deployed [4–7]. The use of AI in everyday life also raises ethical collisions, and human rights principles and legislation must play a key role in addressing these ethical challenges [8–10]. The rapid devel opment of AI presents many opportunities and challenges for the human race. As AI becomes more autonomous and intelligent, it has the potential to greatly improve the performance of manufacturing and service systems, as well as contribute to social development and human life [2, 11, 12, 13]. However, the hardware and software of a fully autonomous, learning, reasoning AI system must mimic the processes and subsystems that exist within the human brain [14, 15].